PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT MEGA FINANCE CABANG FATMAWATI JAKARTA SELATAN - Artanti, Alfayana Yovinza; Ma'fiyah (Journal of Research and Publication Innovation, 2024)
This study aims to determine the influence of the work environment and work discipline on employee performance at PT. Mega Finance Fatmawati South Jakarta Branch either partially or simultaneously. The method used is quantitative descriptive. The population in this study is all employees at PT. Mega Finance Fatmawati Branch South Jakarta sampling technique using saturated sampling and obtained samples in this study amounted to 68 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis tests. The result of this study is that the work environment has a positive effect on Employee Performance with the regression equation Y = 24.985 + 0.395X1, the value of the correlation coefficient is obtained at 0.392 meaning that the two variables have a low relationship. The coefficient of determination is 15.3%. The T test obtained tcount>ttable is 3.458>1.670. So it can be concluded that Ha1: r ≠ 0, this shows that there is a positive influence between the work environment on employee performance. Work discipline positively affects employee performance with the regression equation Y = 16.195 + X2. The value of the correlation coefficient is 0.629 which means that both variables have a strong level of connection. The coefficient of determination is 39.6%. The T test obtained tcount>ttable which is 6.573>1.670. So it can be concluded that Ha2: r ≠ 0, this shows that there is an influence between work discipline on employee performance. Work environment and work discipline on employee performance simultaneously affect employee performance with regression equation Y = 12.589 + 0.156X1 + 0.694X2. The correlation loefficient value of 0.644 means that the variables of work environment and work discipline have a very strong level of relationship to employee performance. The coefficient of determination is 41.5%. Test F obtained Fcalculate > Ftable which is 23.083 > 3.13. So it can be concluded Ha3: r ≠ 0, this shows that there is a simultaneous influence between the work environment and work discipline on employee performance.